Cerebral venous sinus thrombosis as a complication of primary varicella infection in a child, case report. (January 2022) - Badour, Maysaa; Shhada, Eman; Hammed, Ali; Baqla, Sameer
Abstract: Introduction and importance: Chickenpox (Varicella) is a benign illness caused by varicella-zoster virus, predominant in childhood. Chicken pox related neurological complications are seen in less than 1% cases of chickenpox. Cerebral Venous thrombosis due to primary (VZV) infection is very rare, and it may occurs secondary to primary or re-activation the virus. Case presentation: We report a case of 5-year-old female complained of ataxia, vomiting, headache, and drowsiness 7 days after the onset varicella zoster infection. She had vesicular lesions with scab over the trunk and limbs. Clinical discussion: Neurological examination revealed left hemiparesis. Her blood counts and metabolic parameters were normal. Computed tomography brain showed hemorrhagic infarct in the left temporo-parietal region. Coagulation profile was normal. Magnetic resonance imaging (MRI) brain revealed hemorrhagic infarct in the same region. Magnetic resonance Venogram showed thrombosis of left transverse sinus and sigmoid sinus and internal jugular vein. VZV- IgG antibody was positive but CSF VZV PCR (Polymerase chain reaction) was found to be negative. Intravenous acyclovir for 15 days, and low-molecular-weight heparin for 3 days overlapped with oral Warfarin for 3months, . After 3 months follow up, the patient experienced a complete recovery. MRI repeated after 3 months showed recanalization of the sinuses. Conclusion: The pathogenic link of occurrence of CSVT after VZV infection is unclear, but some articles showed that it is related to direct endothelial damage by the virus. Early recognition of this complication of VZV infection and prompt treatment is essential to prevent catastrophic complications. Highlights: Chickenpox (Varicella) is a benign illness caused by varicella-zoster virus, predominant in childhood. Cerebral Venous thrombosis due to primary (VZV) infection is very rare. The pathogenic link of occurrence of CSVT after VZV infection is unclear.